Unraveling Functional Impairment: Exploring Associated Factors Among Trauma-Treated Refugees - Mammadova,Malika; Rohrberg,Julie (2024)
Objective: Mental health is a key concern among refugees, yet treatment response to standardized interventions varies. Functioning is a clinically significant outcome that has been shown to explain individual differences in treatment response. The current study examined functional impairment among trauma-exposed refugees receiving treatment in Denmark. It explored the relationship of various pre- and post-migration factors with functioning and tested the interaction between potentially traumatic events (PTEs) and head trauma. Method: Pre-treatment data from the Danish Trauma Database (DTD) was analyzed via descriptive analysis (N = 2083), two network analysis models (N = 532, N = 463), and multiple linear regression (N = 428). The primary outcome of functioning was measured via the 12-item version of the WHO Disability Assessment Schedule 2.0 (WHODAS 2.0). Results: The network analysis revealed no direct association between functioning and PTEs or head trauma but a range of post-migration factors, most prominently occupation, mediated their relationship with functioning. The regression analysis found a significant effect of head trauma and covariates of age, gender, and country of origin on functioning. However, PTEs and the interaction between PTEs and head trauma were not significant predictors in the regression models. Conclusion: The study findings are in line with the theory that daily stressors may be just as or more important in their contribution to functioning as pre-migration trauma. Understanding the influence of daily stressors on functioning has important implications for treatment, where a multi-service approach that addresses social and economic stressors has the potential to improve treatment response.
Keywords: refugees; functioning; WHODAS 2.0; trauma; head trauma; network analysis; post-migration stressors